2021
DOI: 10.1051/0004-6361/202140642
|View full text |Cite
|
Sign up to set email alerts
|

TMC-1, the starless core sulfur factory: Discovery of NCS, HCCS, H2CCS, H2CCCS, and C4S and detection of C5S

Abstract: We report the detection of the sulfur-bearing species NCS, HCCS, H2CCS, H2CCCS, and C4S for the first time in space. These molecules were found towards TMC-1 through the observation of several lines for each species. We also report the detection of C5S for the first time in a cold cloud through the observation of five lines in the 31–50 GHz range. The derived column densities are N(NCS) = (7.8 ± 0.6)  ×  1011 cm−2, N(HCCS) = (6.8 ± 0.6)  ×  1011 cm−2, N(H2CCS) = (7.8 ± 0.8)  ×  1011 cm−2, N(H2CCCS) = (3.7 ± 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 63 publications
5
25
1
Order By: Relevance
“…Our results build on top of the studies unveiling the chemistry of sulfur in the ISM. Past and recent interstellar searches of saturated (Linke et al 1979;Kolesniková et al 2014;Rodríguez-Almeida et al 2021) and unsaturated (Fuente et al 2017;Martin-Drumel et al 2019;Cernicharo et al 2021;Rodríguez-Almeida et al 2021) S-bearing molecules present a scenario with many mysteries in their formation routes, each one of them contributing to understanding the amount of elemental sulfur locked in organosulfur compounds (Laas & Caselli 2019). In previous studies Lamberts (2018) showed that hydrogenation to saturation of CS is possible in astronomical timescales, indicating that highly saturated species (such as CH 3 SH or C 2 H 5 SH) must be prevalent in later stages of a molecular cloud life.…”
Section: Discussionmentioning
confidence: 99%
“…Our results build on top of the studies unveiling the chemistry of sulfur in the ISM. Past and recent interstellar searches of saturated (Linke et al 1979;Kolesniková et al 2014;Rodríguez-Almeida et al 2021) and unsaturated (Fuente et al 2017;Martin-Drumel et al 2019;Cernicharo et al 2021;Rodríguez-Almeida et al 2021) S-bearing molecules present a scenario with many mysteries in their formation routes, each one of them contributing to understanding the amount of elemental sulfur locked in organosulfur compounds (Laas & Caselli 2019). In previous studies Lamberts (2018) showed that hydrogenation to saturation of CS is possible in astronomical timescales, indicating that highly saturated species (such as CH 3 SH or C 2 H 5 SH) must be prevalent in later stages of a molecular cloud life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hydrocarbons (closed shells and radicals) and their cyano and ethynyl derivatives, TMC-1 revealed itself as an efficient sulfur factory, through the identification of a number of complex sulfur-bearing species in the QUIJOTE survey: HC 3 S + , HCCS, NCS, H 2 CCS, H 2 CCCS, C 4 S, HCSCN, and HCSCCH (Cernicharo et al, 2021h;Cernicharo et al, 2021i).…”
Section: Complex Organic Molecules In the Dark Cloud Tmc-1mentioning
confidence: 99%
“…4), with the HCOCH 2 CN value indicating an upper limit. We compare with other sources: several positions also in the Sgr B2 region (magenta; Brünken et al 2010, see also Marcelino et al 2010); several dense cores (B1-b, L1544, L183, L483) and the lukewarm corino L1527 (green: Marcelino et al 2010;Marcelino et al 2018); the dark cloud TMC-1 (yellow; Cernicharo et al 2021); and the IRAS 16293-2422 B hot corino (red, Zeng et al 2019). To derive the uncertainties of the molecular abundances we have considered the uncertainties of the molecular column densities reported in the different works, or a 15% of the value of N if the uncertainty is not provided, and we assumed an uncertainty for the N (H 2 ) column densities of 15%.…”
Section: Oxygen-bearing Nitrilesmentioning
confidence: 99%